A human rights analysis of the impact of the COVID-19 response on adolescent girls’ sexual and reproductive health rights in Kenya - Nkatha, Murungi (University of Pretoria, 2025)
Mini Dissertation (MPhil (Sexual and Reproductive Rights in Africa))--University of Pretoria, 2024.